Rhizobia: from saprophytes to endosymbionts - Poole, Philip; Ramachandran, Vinoy; Terpolilli, Jason (Nature reviews. Microbiology, 2018)
Key Points Root secretion and plant immunity are key factors in controlling the assembly of root-associated microbiotas of which rhizobia are key members Rhizobia exist in soil and compete with the general microbiota before infecting legumes, typically through root hairs, and forming N 2 -fixing bacteroids Rhizobia have complex pan-genomes. Some strains also have large plasmids or symbiosis islands, which are crucial for fitness, nodulation and N 2 fixation Rhizobia have specific host plants, which makes them excellent models for studying the mechanisms, timing and location of root colonization in host and non-host plants Some legumes, such as members of the invert repeat lacking clade, produce up to several hundred antimicrobial peptides to control bacteroid cell division and development Bacteroids receive carbon as dicarboxylates from legumes, and in exchange, they fix N 2 in a low O 2 environment and secrete ammonia to the plant. Bacteroids must balance electron flow to nitrogenase, lipids, polyhydroxybutyrate and O 2 , and coordinate this process with reductant production by the tricarboxylic acid (TCA) cycle Rhizobia can exist as both free-living soil microbiota and plant-associated endosymbionts, which form N 2 -fixing root nodules. In this Review, Poole, Ramachandran and Terpolilli explore the drastic lifestyle shift that underlies this transition and the associated plant–bacteria interactions. Rhizobia are some of the best-studied plant microbiota. These oligotrophic Alphaproteobacteria or Betaproteobacteria form symbioses with their legume hosts. Rhizobia must exist in soil and compete with other members of the microbiota before infecting legumes and forming N 2 -fixing bacteroids. These dramatic lifestyle and developmental changes are underpinned by large genomes and even more complex pan-genomes, which encompass the whole population and are subject to rapid genetic exchange. The ability to respond to plant signals and chemoattractants and to colonize nutrient-rich roots are crucial for the competitive success of these bacteria. The availability of a large body of genomic, physiological, biochemical and ecological studies makes rhizobia unique models for investigating community interactions and plant colonization.